Educação matemática na educação profissional de nível médio: análise sobre possibilidades de abordagens interdisciplinares - Gonçalves, Harryson Júnio Lessa [UNESP]; Pires, Célia Maria Carolino (Universidade Estadual Paulista (Unesp), Programa de Pós-Graduação em Educação Matemática, 2014)
In this article we aim to broaden the discussion about mathematical education of students of Middle Level Professional Education in Brazil (EPTNM), focusing on the issue of interdisciplinarity, emphasized in official documents as one of the organizing axes of the curriculum for this type of education. Studies in this field are justified by the growth of this modality in the Brazilian educational system, as well as the lack of specific investigations in the field of Mathematics Education about it. Our research is guided by the questions: Can the adoption of an interdisciplinary approach to organizing the curriculum contribute to building links between technical professional education and the more academic education characteristic of Middle Level education? What are its potentialities for promoting more meaningful learning of mathematical content in this type of education? We conclude that the superficiality with which the theme of interdisciplinarity has been handled, and the lack of contextualization in other research related to it in mathematics education, are some of the reasons for not implementing the idea successfully. In this article, we discuss the contribution of different authors who research the theme and include proposals to explore Ethnomathematics and Modeling as possibilities for curriculum enrichment of the EPTNM, linking different areas of knowledge and contextualizing math in the reality of the world of work.

No presente artigo nosso objetivo é ampliar a discussão sobre a educação matemática de alunos da Educação Profissional de Nível Médio no Brasil (EPTNM), focalizando a questão da interdisciplinaridade, apontada em documentos oficiais como um dos eixos organizadores dos currículos para essa modalidade de ensino. Estudos nesse campo justificam-se, tanto pela dimensão que essa modalidade vem tomando no sistema educacional brasileiro, como pela carência de investigações específicas na área de Educação Matemática sobre EPTNM. Nossa investigação orienta-se pelas questões: a adoção de uma perspectiva de organização curricular interdisciplinar pode contribuir para a articulação entre a formação profissional técnica e a formação mais acadêmica como é colocada para o Ensino Médio? Quais suas potencialidades para a constituição de aprendizagens mais significativas de conteúdos matemáticos nessa modalidade de ensino? Avaliamos que a superficialidade com que o tema da interdisciplinaridade tem sido tratado e a falta de sua contextualização no âmbito das demais pesquisas em Educação Matemática são alguns dos fatores da não implementação da ideia com sucesso. Nesse sentido, neste artigo, retomamos a contribuição de diferentes autores que investigam o tema e incluímos proposições no sentido de explorar a Etnomatemática e a Modelagem como possibilidades de enriquecimento curricular da EPTNM, articulando diferentes áreas do conhecimento e contextualizando a matemática na realidade do mundo do trabalho.
Mathematical education in mid-level professional education: analysis of opportunities for interdisciplinary approaches
Keywords: Educação Profissional; Currículos de Matemática; Interdisciplinaridade; Modelagem Matemática; Professional Education; Math Curriculum; Interdisciplinarity; Mathematical Modeling